1976
DOI: 10.1039/c39760001011
|View full text |Cite
|
Sign up to set email alerts
|

SN2? catalysis and sulphene formation

Abstract: Ethenesulphonyl chloride reacts with a mixture of a tertiary amine and an alcohol by SN2' attack of the amine to form the positively charged sulphene which then gives a mixture of the ethenesulphonate and 2-trialkylammonioethanesulphonate esters.THE formation of alkyl ethenesulphonates (2) by the reaction of ethenesulphonyl chloride (1) with alcohols in the presence of a tertiary amine is apparently unreported, even though compounds (2) are made under similar conditions from 2-chloroethanesulphonyl chloride,' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The former description, though brief, appears to convey an unintended implication that the reaction is necessarily concerted, and we therefore now use the less connotative term "vinylogous nucleophilic catalysis". Our first experiments and communication (17) investigated esterification in nonpolar media, but subsequent work on the hydrolysis has provided a system which, because it is simpler in its chemistry and easier to study kinetically, now appears to be the logical starting point for a detailed presentation of the mechanism of the reaction; the esterification reactions will be discussed in a subsequent paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The former description, though brief, appears to convey an unintended implication that the reaction is necessarily concerted, and we therefore now use the less connotative term "vinylogous nucleophilic catalysis". Our first experiments and communication (17) investigated esterification in nonpolar media, but subsequent work on the hydrolysis has provided a system which, because it is simpler in its chemistry and easier to study kinetically, now appears to be the logical starting point for a detailed presentation of the mechanism of the reaction; the esterification reactions will be discussed in a subsequent paper.…”
Section: Resultsmentioning
confidence: 99%
“…As we show in this paper, the simple tertiary amine-promoted hydrolysis of ethenesulfonyl chloride does, in fact, proceed by a "path 6" mechanism. In preliminary communications (17,18) we have already outlined this and a related study of the corresponding reaction with alcohols in a nonpolar medium, and used the terms "SN2' catalysis" and "vinylogous nucleophilic catalysis" for the "path b" process. The former description, though brief, appears to convey an unintended implication that the reaction is necessarily concerted, and we therefore now use the less connotative term "vinylogous nucleophilic catalysis".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Truce and Campbell (8) had looked at the action of triethylamine and alcohols on 1 -propene-1 -sulfonyl chloride and had noted the formation of both the 1 -propene-and 2-propenesulfonate esters, CH3CH=CHS020R and CH2= CHCH2S020R. In our first experiments (13), simple mixing of 1 with 2-propanol in the presence of pyridine or trimethylamine followed by conventional work-up gave the ethenesulfonate ester (5, R = Pri) in mediocre (40-50%) yield. To find out what had happened to the rest of the material, we examined the product directly by 'Hrnr, which showed the presence of about 60% of the ester (5, R = Pri) along with another product (-40%), which appeared to be Me3N+CH2CH2S020Pri C1-(6), i.e.…”
Section: Initial Experiments and Related Workmentioning
confidence: 99%
“…This last process was unknown at the time, but we have subsequently shown that this can be the chief route of the tertiary amine promoted hydrolysis of 1-alkenesulfonyl chlorides (1 1, 12). The present paper describes extension of this work to the reaction of alcohols with tertiary amines and 1-alkenesulfonyl chlorides; a preliminary report of the earliest stages has appeared (13).…”
Section: Introductionmentioning
confidence: 99%